Pathways for Sustainable Urban Waste Management and Reduced Environmental Health Risks in India: Winners, Losers, and Alternatives to Waste to Energy in Delhi - Randhawa, Pritpal; Marshall, Fiona; Kushwaha, Pravin Kumar; Desai, Pranav (Frontiers in Sustainable Cities, 2020)
This paper examines the shift towards centralized waste-to-energy (WTE) as a singular solution to Delhi’s solid waste crisis and describes a transdisciplinary research process that sought to understand how and why this dominant waste management pathway emerged. It also sought to engage with and facilitate debate on the potential for alternative waste management pathways, which may better address combined environmental and social justice concerns. We explain the emergence of a transforming narrative that reframed waste from a risk to a resource, reflecting and reinforcing the dominant trajectory of socio-technical-ecological change in urban development, and reconfiguring waste related infrastructure to involve public private participation and WTE technology. Drawing on empirical studies, involving local residents, wastepickers associations, NGOs, and government officials, we discuss implications of WTE projects in Delhi. We argue that the current WTE focused approach, without modification, may simply displace health hazards across time, space and social groups and exacerbate social justice concerns. The dominant narrative on waste management priorities appear to make certain health risks protected and recognized whilst others are made invisible. We make the case for possible alternative waste management scenarios, institutional and regulatory arrangements that may better address environmental health and social justice concerns. These are summarized under eight principles for reframing urban waste management policy challenges in the context of sustainable urban development. These principles include a reframing of waste management through a sustainability lens that links currently divergent initiatives on environmental health and social justice. It involves an appreciation of complex socio-material flows of waste, the need to move beyond perspectives of waste management as an environmental policy issue alone, appreciation in policy development that the informal sector will remain a key player despite attempts to formalize waste management and the need to provide incentives for diverse waste management strategies that move beyond the private.